What impacts the value of revenues from taxation of income of corporations? Evidence from European Union Member States - Karpowicz, Andrzej (University of Wroclaw. Faculty of Law, Administration & Economics, 2022)
Fiscal revenues from taxation of income of corporations are more volatile than those earned from any other mayor tax. COVID-19 and the war in Ukraine pose additional threats to government inflows from this source, especially jeopardizing several EU Member States and Eurozone countries struggling with piling public debts, but at the same time maintaining common monetary policy. Therefore, there is a need for better management of revenues from corporate income tax in periods going forward. The aim of this study is to explain the impact of the level of budget inflows from taxation of income of corporations. It turns out that countries are indeed able to influence revenues from this tax by shaping the statutory tax rates. However, most determinants cannot be influenced directly by governments – such as GDP, level of globalization, R&D expenditures, total employment, age dependency ratio, or public debt. Although some of these phenomena are out of control in the short term, states may consider affecting their levels through appropriate economic policy led in the long run. This study is performed for panel data encompassing 16 potential determinants of corporate income tax revenues for all EU Member States from 1995 to 2020, which is the longest period ever considered for such a set of countries that concurrently includes first aftermaths posed to the economy by COVID-19.
Keywords: corporate income tax; fiscal policy; tax management; macroeconomics